Analysis of Fund Management and Allocation Strategies in Islamic Banking - Nur Shafiqah; Rahmi; Ayu Ariska (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2026)
Fund management is a fundamental aspect of maintaining the stability and operational sustainability of banks. This study aims to examine various sources of bank funds, including core funds (capital) and external funds, and how the allocation of these funds is managed to support the intermediation function. The research method used is a literature review (library research) by analyzing secondary data from various scientific literature, books, and articles related to banking management. The results indicate that core funds derived from paid-in capital, reserves, and retained earnings serve as a risk buffer and an indicator of a bank’s health. Meanwhile, external funds mobilized from the public through savings, checking accounts, and deposits, as well as funds from financial institutions and investors, are the primary instruments for expanding financing capacity. Effective fund allocation requires a balanced strategy between loans, investments, and liquidity reserves to maintain public confidence and to comply with regulatory requirements. Thus, the integration of capital adequacy and proper fund allocation management is key to maintaining the integrity of the banking financial reporting system